RESTRICTIONS ON THE DECENTRALIZATION OF RENEWABLE ENERGY IN BULGARIA: RESTRICTIONS ON THE DECENTRALIZATION OF RENEWABLE ENERGY IN BULGARIA - Nikolova, Ralitsa (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The promotion of decentralized systems for renewable energy is one of the key moments in the proposals for a new EC energy policy. In the recent years, despite the encouragement by the law, their development has been restricted which has required rethinking both the existing incentives and overcoming some barriers. This article identifies these barriers existing before the development of the decentralized renewable energy production in Bulgaria and provides recommendations on how these could be overcome based on the good practice of the other countries.